Wasted bodies : a gendered critique of the Dalit consciousness through 'waste' in select Dalit autobiographies - Saraniyah Saravanan (Nanyang Technological University, 2021)
This paper navigates the limitations of the Dalit consciousness in emancipating the rural Dalit population in India. It is well-documented that urban commercial activities have contributed to the relegation of excessive garbage to the margins of society –– rural spaces. Rural Dalit women in particular have borne the burden of the violence that comes with this marginality. This study asks how the Dalit consciousness has dealt with this divide (or has not). It delivers a critique on the Dalit consciousness through the use of Dalit autobiographies. I focus specifically on the Mahar Dalit castes in rural Maharashtra from the early-to-late twentieth century; and their autobiographical texts’ reliance on the aesthetics of ‘waste’ to authenticate the rural experience of casteism. This study adopts interpretive frameworks of ‘waste’, space and gender in order to unpack how hegemonic notions of garbage and filth are used to extort labour and resources from the rural space. This is a historical and literary study that is critical of the physical and metaphorical manifestation of waste in the reading of Dalit narratives. Ultimately, it is argued that the naturalisation of the Dalits relations with waste reproduces caste violence on rural Dalit women.